2012
DOI: 10.1126/science.1226630
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Molecular Evolution in an Herbivore Community

Abstract: Numerous insects have independently evolved the ability to feed on plants that produce toxic secondary compounds called cardenolides and can sequester these compounds for use in their defense. We surveyed the protein target for cardenolides, the alpha subunit of the sodium pump, Na+,K+-ATPase (ATPα), in 14 species that feed on cardenolide-producing plants and 15 outgroups spanning three insect orders. Despite the large number of potential targets for modulating cardenolide sensitivity, amino acid substitutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
414
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(441 citation statements)
references
References 73 publications
(47 reference statements)
25
414
1
1
Order By: Relevance
“…third trophic level) [1,24,35]. Although some specialist herbivores have overcome host defences [42,43], plants are thought to evolve defences in response to multiple herbivores and rates of damage should indicate investment in resistance [16]. While it is possible that alternative evolutionary processes could produce patterns that are consistent with the OU model, for example, fluctuating selection on investment in defence, it is not clear how such processes would result in the observed strong differences in herbivory rates among major plant lineages and on plants with different growth forms.…”
Section: Resultsmentioning
confidence: 99%
“…third trophic level) [1,24,35]. Although some specialist herbivores have overcome host defences [42,43], plants are thought to evolve defences in response to multiple herbivores and rates of damage should indicate investment in resistance [16]. While it is possible that alternative evolutionary processes could produce patterns that are consistent with the OU model, for example, fluctuating selection on investment in defence, it is not clear how such processes would result in the observed strong differences in herbivory rates among major plant lineages and on plants with different growth forms.…”
Section: Resultsmentioning
confidence: 99%
“…Describing widespread parallel evolution on armour plating in wild threespine sticklebacks, Colosimo et al 15 demonstrated the Ectodysplasin signalling pathways to be repeatedly targeted for modifications to this phenotype with a high degree of site-specific parallel evolution. Looking across 14 insect species that feed on cardenolide-producing plants, Zhen et al 45 also noted repeated bouts of parallel evolution for dealing with this toxicity not only confined to the same alpha subunit of the sodium pump (ATPa), but in the great majority of cases to the same two amino acid positions. Examining adaptation to pesticide resistance in Drosophila, four specific point mutations in the Ace gene have been identified, which result in resistance to organophosphates and carbonates (see ref.…”
Section: Box 3 | Expectations and Assumptions Of A Model Of Multiple mentioning
confidence: 99%
“…All docking simulations were performed with AutoDock vina 2.0 (55) using an approach similar to that described by Zhen et al (8). To establish a docking protocol we first redocked the cardiac glycoside bufalin into the crystal structure of bufalin bound to the pig Na (27).…”
Section: −7mentioning
confidence: 99%
“…Epitomized by the writings of Gould (5) and Conway Morris (6), this debate centers on whether evolution is stochastic and unpredictable (5) or subject to constraints that limit the available options for evolution, resulting in frequent convergence and a degree of predictability (6). However, evidence of convergence at the genetic level, where similar molecular changes confer the same change in phenotype, is currently limited to only a few taxonomically restricted examples (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%